Extensive diversity in the allelic frequency of Plasmodium falciparum merozoite surface proteins and glutamate-rich protein in rural and urban settings of southwestern Nigeria - Roland I. Funwei; Bolaji N. Thomas; Catherine O. Falade; Olusola Ojurongbe (Malaria Journal, 2018)
Abstract Background Nigeria carries a high burden of malaria which makes continuous surveillance for current information on genetic diversity imperative. In this study, the merozoite surface proteins (msp-1, msp-2) and glutamate-rich protein (glurp) of Plasmodium falciparum collected from two communities representing rural and urban settings in Ibadan, southwestern Nigeria were analysed. Methods A total of 511 febrile children, aged 3–59 months, whose parents/guardians provided informed consent, were recruited into the study. Capillary blood was obtained for malaria rapid diagnostic test, thick blood smears for parasite count and blood spots on filter paper for molecular analysis. Results Three-hundred and nine samples were successfully genotyped for msp-1, msp-2 and glurp genes. The allelic distribution of the three genes was not significantly different in the rural and urban communities. R033 and 3D7 were the most prevalent alleles in both rural and urban communities for msp-1 and msp-2, respectively. Eleven of glurp RII region genotypes, coded I–XII, with sizes ranging from 500 to 1100 base pairs were detected in the rural setting. Genotype XI (1000–1050 bp) had the highest prevalence of 41.5 and 38.5% in rural and urban settings, respectively. Overall, 82.1 and 70.0% of samples had multiclonal infection with msp-1 gene resulting in a mean multiplicity of infection (MOI) of 2.8 and 2.6 for rural and urban samples, respectively. Msp-1 and msp-2 genes displayed higher levels of diversity and higher MOI rates than the glurp gene. Conclusion Significant genetic diversity was observed between rural and urban parasite populations in Ibadan, southwestern Nigeria. The results of this study show that malaria transmission intensity in these regions is still high. No significant difference was observed between rural and urban settings, except for a completely different msp-1 allele, compared to previous reports, thereby confirming the changing face of malaria transmission in these communities. This study provides important baseline information required for monitoring the impact of malaria elimination efforts in this region and data points useful in revising current protocols.